Rent-Seeking. Zur politischen Theorie des neoklassischen Fundamentalismus - Elkins, Stephan (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1994)
The concept is concerned with economic inefficiency and stagnation contrived by government intervention into the economic process. The prospect of profiting from political intervention encourages rational actors to shift their efforts from productive activities to political manipulation, inducing a substantial reduction in aggregate levels of social welfare. This leads to the conclusion that the restoration of society’s productive capacities requires wresting the economy from the clutches of the state occupied by special interests. The author criticizes this analysis on account of an inadequate political theory based on the framework of neoclassical economics. Moreover, the notion that »depoliticization of the economy« could provide asolution to the problem of »rent-seeking« is shown tobe inconsistent and sociologically naive. An adequate analysis of the problems related to »rent-seeking« should to take the specific selectivity of political institutions, which favours specific interests and policy issues, as its starting point.